مقارنة السلوك الزلزالي للمداخن البيتونية المسلحة الصناعية الأسطوانية والمخروطية - طريفي زكائي (Latakia University Journal -Engineering Sciences Series, 2015)
تُعَدُّ المداخن البيتونية المسلحة من المنشآت الصناعية المهمة، وتأخذ أشكالاً هندسية مختلفة في المقطع الطولي. تم في البحث مقارنة السلوك الزلزالي بين المداخن الأسطوانية والمخروطية، حيث تم اعتماد مدخنتين متطابقتين في الارتفاع، ومتكافئتين في القطر وسماكة الجدار. تمت النمذجة بالاعتماد على برنامج SAP 2000 . طبقت الحمولة الزلزالية بشكل استاتيكي مكافئ، وبطريقة طيف الاستجابة، ومن ثم بطريقة السجل الزمني؛ حيث تم حساب قوى القص والعزوم على ارتفاع المداخن . تم الاستنتاج بأن قوى المقطع المتشكلة نتيجة الزلازل أكبر في حالة المدخنة المخروطية منها في حالة المدخنة الاسطوانية المكافئة لها، حيث زادت قيم قوى القص والعزوم بحوالي 33% عند اعتماد طريقة طيف الاستجابة . وتم الاستنتاج في ختام البحث بأنه للتخفيف من القوى الناجمة عن الزلازل ينصح باعتماد المداخن البيتونية الاسطوانية في المقطع الطولي . It is considered that reinforced concrete chimneys are very important industrial Structures. Concrete Chimneys take different geometric shapes in Longitudinal section. In these Paper we compared the seismic behavior between cylindrical and conical chimneys. Where was adopted cylinder chimney other conical identical to rise, and equivalent in diameter and wall thickness. Modeling has bin done for two chimneys according to Program SAP 2000 . Seismic load applied as equivalent static, response spectrum method, and as time history, were was calculated shear forces and moments over the high of both chimneys. It was conclusion that the cross section resulted by effect of earthquakes in the case of conical chimney is greater than case of equivalent cylindrical chimney. Where increased the values of shear forces and moments about 33% by using the response spectrum method. It was concluded at the end of the research as to mitigate the forces caused by earthquakes advised the adoption of concrete cylindrical chimneys in longitudinal section. Keywords: Industrial chimneys, Reinforced concrete chimneys, earthquake performance, response spectrum, equivalent Static method, SAP 2000 Software .